تقييم جودة خدمات التأمينات البنكية الفلاحية - مناد, منال (My University, 2024)
This study aimed to evaluate the quality of agricultural banking insurance services through a case study of the agricultural development bank of Mesra-Mostganem branch. To test the hypotheses, the study employed a descriptive-analytical approach, distributing a questionnaire to a sample of 30 customers who benefit from agricultural banking insurance. The Excel program was used to analyse the collected data. The study reached the following conclusions: - According to the customer’s evaluation, the quality of agricultural banking insurance services provided by the bank under study was satisfactory and met their expectations, obtaining very high scores on all indicators. - However, some customers had comments about adding and improving some insurance services, especially regarding the promotion of digitization and providing speed in dealing with customer.
وكالة ماسرى مستغانم BADRدراسة حالة بنك الفلاحة والتنمية الريفية وكالة
Keywords: Evaluation, service Quality, Agricultural Banking Insurance, Agricultural Bank.